Uranium adsorption resin as well as preparation method and application thereof
By preparing uranium adsorption resin, using materials such as acrylonitrile, alkyl acrylate and divinylbenzene, combined with the reaction of ethylenediamine, 2-bromobenzimidazole and amidoximetization reagent, the existing uranium adsorption materials in seawater are solved. The problems of low uranium concentration and low adsorption efficiency and insufficient antibacterial performance in complex environments have achieved efficient uranium adsorption and good antibacterial performance.
Patent Information
- Application Number
- CN202411658336.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-07
AI Technical Summary
The existing uranium adsorbent materials have low adsorption efficiency and insufficient antibacterial properties in seawater, making it difficult to effectively increase uranium in seawater under low uranium concentration and complex environments.
By preparing a uranium adsorption resin, a mixture of acrylonitrile and alkyl acrylate is formed with divinyl benzene to form terpolymerized microspheres, and ethylenediamine, 2-bromobenzimidazole and aminoximation reagent The reaction is to form an uranium adsorption resin with high uranium adsorption ability and antibacterial rate.
It has achieved high efficiency uranium adsorption and good antibacterial properties of uranium adsorption resin in seawater, with high ball grinding rate and good mechanical strength.
Smart Images

Figure BDA0005142642860000081
Abstract
Description
Technical Field
[0001] The invention relates to a uranium adsorption resin and a preparation method and application thereof. Background Art
[0002] Natural uranium is the basic raw material for nuclear energy and a non-renewable radioactive mineral resource. In order to ensure the development of the nuclear energy industry, it is necessary to explore new uranium resources. The total amount of uranium in global seawater is about 4.5 billion tons, and seawater has high mobility and no geographical restrictions, so it is a shared resource. If seawater uranium extraction technology can be economically feasible, it can effectively ensure the sustainable supply of natural uranium resources in my country.
[0003] Since the 1960s, people have begun to study methods for extracting uranium from seawater. Among them, adsorption is one of the most studied and most feasible methods. The key to the adsorption method is the preparation of adsorption materials. The uranium concentration in seawater is very low (about 3.3μg / L), there are many ions coexisting with uranium, and the marine environment is relatively complex. In particular, the existence of biological attachment will seriously interfere with the material's uranium adsorption process and reduce the material's uranium adsorption capacity.
[0004] CN113713783A discloses a method for preparing benzimidazole-amidoxime fiber, comprising the following steps: (1) reacting 5 parts by weight of acrylonitrile-methyl acrylate copolymer fiber with 1 to 15 parts by weight of an amine reagent to obtain an aminated fiber; wherein the amine reagent is selected from one or more of ethylenediamine, triethylenetetramine, and dimethylamine; (2) reacting 5 parts by weight of the aminated fiber with 3 to 20 parts by weight of 2-bromobenzimidazole to obtain a benzimidazole functionalized fiber; (3) reacting 5 parts by weight of the benzimidazole functionalized fiber with 10 to 40 parts by weight of hydroxylamine hydrochloride to obtain a benzimidazole-amidoxime fiber. This method uses acrylonitrile-methyl acrylate copolymer fiber as a raw material, and there are problems in the preparation process such as fiber gelation and loss that affect material preparation and mechanical strength, and the antibacterial rate of the obtained product still needs to be improved. Summary of the invention
[0005] In view of this, one object of the present invention is to provide a method for preparing a uranium adsorption resin. The prepared uranium adsorption resin has both good uranium adsorption capacity and antibacterial rate, and has a high ball milling rate. Another object of the present invention is to provide a uranium adsorption resin prepared by the above preparation method. Another object of the present invention is to provide the use of the above uranium adsorption resin.
[0006] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0007] In one aspect, the present invention provides a method for preparing a uranium adsorption resin, comprising the following steps:
[0008] 1) 80 to 98 parts by weight of acrylonitrile and 2 to 20 parts by weight of alkyl acrylate are mixed to form a mixed solution, and then the mixed solution is mixed with 10 to 45 parts by weight of divinylbenzene to obtain a mixture; wherein the number of alkyl carbon atoms of the alkyl acrylate is 1 to 5; 100 parts by weight of the mixture, 60 to 200 parts by weight of a porogen and 0.5 to 2 parts by weight of an initiator are mixed to form an organic phase; gelatin, sodium chloride and water are mixed in a weight ratio of 1 to 3:10 to 30:100 to 300 to obtain an aqueous phase; the organic phase and the aqueous phase are mixed in a volume ratio of 1:2 to 1:5, reacted at 60 to 85°C for 2 to 6 hours, and then cured at 70 to 90°C for 8 to 12 hours to obtain ternary copolymer microspheres; wherein the porogen is selected from at least one of toluene and isooctane; the initiator is selected from at least one of benzoyl peroxide and azobisisobutyronitrile;
[0009] 2) reacting the ternary copolymer microspheres with ethylenediamine at 60 to 120° C. for 1 to 24 hours to obtain aminated microspheres; wherein the mass ratio of the ternary copolymer microspheres to ethylenediamine is 1:0.2 to 1:2;
[0010] 3) reacting the aminated microspheres with 2-bromobenzimidazole in a reaction solvent containing a catalyst at 40 to 80° C. for 10 to 48 hours to obtain functionalized microspheres; wherein the mass ratio of the aminated microspheres to the 2-bromobenzimidazole is 1:0.5 to 1:3; the reaction solvent is a C1 to C5 alkyl alcohol, and the catalyst is a tertiary amine containing three C1 to C5 alkyl groups;
[0011] 4) adding the functionalized microspheres to a solution containing an amine oximation reagent, reacting at 60 to 80° C. for 8 to 48 hours to obtain a uranium adsorption resin; wherein the mass ratio of the functionalized microspheres to the amine oximation reagent is 1:1 to 1:6; and the amine oximation reagent is selected from at least one of hydroxylamine hydrochloride and hydroxylamine sulfate.
[0012] In the mixed solution in step 1), the weight portion of acrylonitrile is preferably 85 to 95 weight portions, the weight portion of alkyl acrylate is preferably 5 to 15 weight portions. The alkyl acrylate is preferably methyl acrylate or ethyl acrylate. The weight portion of divinylbenzene as a cross-linking agent is preferably 15 to 30 weight portions.
[0013] In step 1), the amount of the porogen is preferably 80 to 120 parts by weight; the porogen is preferably toluene or isooctane. The amount of the initiator is preferably 0.8 to 1.5 parts by weight; the initiator is preferably benzoyl peroxide or azobisisobutyronitrile.
[0014] According to one embodiment of the present invention, in step 1), the volume ratio of the organic phase to the aqueous phase is preferably 1:3 to 1:4.
[0015] According to the preparation method of claim 1, preferably, in step 1), the weight ratio of gelatin, sodium chloride and water is 2-3:20-30:200-230. The water can be deionized water or ultrapure water, more preferably deionized water.
[0016] In the present invention, the reaction temperature in step 1) is preferably 65-80°C; the reaction time is preferably 3-5 hours. The curing temperature in step 1) is preferably 75-85°C; the curing time is preferably 9-10 hours.
[0017] According to one embodiment of the present invention, step 1) may further include washing and extracting the reaction product to obtain ternary copolymer microspheres.
[0018] Deionized water or ultrapure water is preferably used for the washing, and deionized water is more preferably used. The washing times may be 1 to 5 times, and preferably 3 to 4 times.
[0019] The extraction can use any extraction method in the art to remove the porogen, and is not particularly limited here. For example, according to one embodiment of the present invention, the Soxhlet extraction method can be used for extraction: ethanol is used as an extractant, and the washed reaction product is extracted in a Soxhlet extractor. During the extraction process, the ethanol is heated, vaporized, rises, condensed, and drips into the extraction tube, and this cycle is repeated until the extraction amount of the porogen no longer increases, and the extraction is completed.
[0020] In step 1), controlling the ratio of the reaction raw materials and the reaction conditions within the above range is conducive to the suspension copolymerization reaction; it is more conducive to the introduction of ester group reaction active sites to generate qualified ternary copolymer microspheres.
[0021] According to the preparation method of the present invention, preferably, in step 2), the ternary copolymer microspheres and the ethylenediamine are reacted in toluene. The toluene is present as a solvent phase, and its amount is not particularly limited as long as it can achieve the stirring of the ternary copolymer microspheres and the ethylenediamine. For example, according to one embodiment of the present invention, toluene can be added in an amount of 20 to 60 mL of toluene per gram of ternary copolymer microspheres; preferably 30 to 50 mL.
[0022] In step 2), the mass ratio of the ternary copolymer microspheres to the ethylenediamine is preferably 1:0.5 to 1:1.5.
[0023] The temperature for the reaction of the ternary copolymer microspheres with the ethylenediamine is preferably 80 to 110° C., and the reaction time is preferably 12 to 20 hours.
[0024] According to one embodiment of the present invention, step 2) may further include filtering, washing and drying the reaction product to obtain aminated microspheres. The filtration may be performed by any filtration method known in the art. The washing is preferably performed by deionized water or ultrapure water, more preferably deionized water. The number of washings may be 1 to 5 times, preferably 3 to 4 times. The drying may be performed by any drying method known in the art; preferably, vacuum drying is performed at 30 to 60°C for 12 to 48 hours.
[0025] In step 2), the ratio of the reaction raw materials and the reaction conditions are controlled within the above range, which is conducive to the amine exchange reaction and is more conducive to the amino functionalization of the ternary copolymer microspheres to generate qualified aminated microspheres.
[0026] According to the preparation method of the present invention, preferably, the C1-C5 alkyl alcohol is a C1-C3 normal alkyl alcohol; more preferably, it is at least one of methanol and ethanol.
[0027] According to the preparation method of the present invention, preferably, the tertiary amine containing three C1-C5 alkyl groups is triethylamine.
[0028] According to the preparation method of the present invention, preferably, in step 3), the catalyst is added in an amount of 0.2 to 0.6 mL of catalyst per gram of aminated microspheres; preferably 0.4 to 0.5 mL.
[0029] In step 3), the temperature for reacting the aminated microspheres with 2-bromobenzimidazole is preferably 50-70° C., and the reaction time is preferably 12-36 hours. The mass ratio of the aminated microspheres to 2-bromobenzimidazole is preferably 1:1-1:2.
[0030] According to one embodiment of the present invention, step 3) may further include filtering, washing and drying the reaction product to obtain aminated microspheres. The filtration may be performed by any filtration method known in the art. The washing is preferably performed by deionized water or ultrapure water, more preferably deionized water. The number of washings may be 1 to 5 times, preferably 3 to 4 times. The drying may be performed by any drying method known in the art; preferably, vacuum drying is performed at 30 to 60°C for 12 to 48 hours.
[0031] In step 3), the ratio of the reaction raw materials and the reaction conditions are controlled within the above range, which is conducive to the substitution reaction and is more conducive to the substitution of the aminated microspheres to generate qualified functionalized microspheres.
[0032] According to the preparation method of the present invention, preferably, in step 4), the preparation method of the solution containing the amine oximation reagent is as follows:
[0033] An amine oximation reagent is added to a mixture of methanol and water, and the pH value of the mixture is adjusted to 6.5 to 7.5, more preferably 7, with an alkali metal hydroxide to obtain a solution containing an amine oximation reagent. The volume ratio of the methanol to water is 1:0.5 to 1:2, more preferably 1:0.8 to 1:1.5. The alkali metal hydroxide is selected from at least one of potassium hydroxide and sodium hydroxide, preferably potassium hydroxide or sodium hydroxide. Deionized water or ultrapure water is used for the water, more preferably deionized water. The alkali metal hydroxide can be added directly or prepared as a solution, which is not limited here.
[0034] In step 4), the temperature for the reaction of the functionalized microspheres with the amine oximation reagent is preferably 65 to 75°C; the reaction time is preferably 12 to 36 hours. The mass ratio of the functionalized microspheres to the amine oximation reagent is preferably 1:3 to 1:5. The amine oximation reagent is preferably hydroxylamine hydrochloride or hydroxylamine sulfate.
[0035] According to the preparation method of the present invention, preferably, in step 4), the reaction product obtained after the reaction is immersed in an alkali metal hydroxide solution with a mass concentration of 1 to 5 wt%, and shaken at 25 to 60° C. for 2 to 8 hours to obtain a uranium adsorption resin. The alkali metal hydroxide in the alkali metal hydroxide solution is selected from at least one of potassium hydroxide and sodium hydroxide.
[0036] More preferably, in step 4), the reactant obtained after the reaction is immersed in an alkali metal hydroxide solution with a mass concentration of 1.5-3wt%, and shaken at 30-55° C. for 3-6 hours to obtain a uranium adsorption resin. The alkali metal hydroxide in the alkali metal hydroxide solution is potassium hydroxide or sodium hydroxide.
[0037] The present invention has no limitation on the amount of the alkali metal hydroxide solution used for immersion, as long as the reaction product can be completely immersed.
[0038] The present invention soaks the reactants obtained after the reaction in an alkali metal hydroxide solution to promote the conversion of functional groups in the reactants into cyclic amidoxime groups, thereby improving the uranium adsorption capacity of the prepared uranium adsorption resin.
[0039] According to one embodiment of the present invention, in step 4), the reaction product may be washed before being soaked in the alkali metal hydroxide solution; after being soaked in the alkali metal hydroxide solution, the reaction product is filtered and washed to obtain the uranium adsorption resin.
[0040] The filtration may be performed by any filtration method known in the art. The washing may be performed by deionized water or ultrapure water, more preferably deionized water. The washing may be performed 1 to 5 times, preferably 3 to 4 times.
[0041] In step 4), the ratio of the reaction raw materials and the reaction conditions are controlled within the above range, which is conducive to the addition reaction and is more conducive to the addition of amidoxime groups to the functionalized microspheres to generate qualified uranium adsorption resin.
[0042] On the other hand, the present invention also provides a uranium adsorption resin prepared by the above preparation method.
[0043] The antibacterial rate of the uranium adsorption resin against Staphylococcus aureus is above 96.8%, preferably above 97%, and the antibacterial rate against Escherichia coli is above 96.2%, preferably above 96.4%.
[0044] The ball milling rate of the uranium adsorption resin is above 91.5%, preferably above 91.8%.
[0045] The uranium adsorption resin has an adsorption capacity of at least 18.5 mg / g of uranium in seawater; preferably at least 19 mg / g.
[0046] When the uranium adsorption resin of the present invention adsorbs uranium in seawater, it has a high antibacterial rate, good antibacterial property, and good uranium adsorption capacity. The uranium adsorption resin of the present invention has a high ball milling rate and good mechanical strength.
[0047] In another aspect, the present invention also provides the use of the uranium adsorption resin in extracting uranium from seawater.
[0048] The present invention introduces alkyl acrylate in suspension copolymerization to provide reactive sites for the introduction of antibacterial groups (benzimidazole) to prepare uranium adsorption resin. The present invention improves the anti-biological adhesion performance of the resin in seawater, the ball milling rate of the prepared resin is high, and the resin has good uranium adsorption capacity. DETAILED DESCRIPTION
[0049] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0050] The "crosslinking degree" mentioned in the present invention refers to the mass percentage of the crosslinking agent in the resin.
[0051] The "uranium adsorption capacity" mentioned in the present invention refers to the amount of uranium adsorbed by a unit adsorbent, and the unit is mg / g.
[0052] The "inhibition rate" mentioned in the present invention refers to the percentage of the difference between the number of colonies without antibacterial treatment and the number of colonies after antibacterial treatment to the number of colonies without antibacterial treatment.
[0053] The "ball milling rate" mentioned in the present invention refers to the ball milling rate after grinding, which refers to the percentage of ball particles in the total amount of the sample after the resin is subjected to abrasion treatment.
[0054] <Ingredients>
[0055] Unless otherwise specified, the raw materials used in the following examples are all commercially available products.
[0056] <Test Method>
[0057] Uranium adsorption capacity test
[0058] Uranyl carbonate was added to natural seawater to a uranium concentration of 3 mg / L, and the pH value was adjusted to 8.1 to obtain spiked seawater. 2L of spiked seawater was added to a conical flask with 0.3g of uranium adsorption resin and adsorbed on a shaker at 25°C for 24h. The uranium content in the resin after adsorption was determined.
[0059] The uranium content is determined according to HJ700-2014.
[0060] Antibacterial performance test
[0061] The antibacterial properties were determined according to the oscillation method in GB / T 20944.3-2008. The bacteria used were Staphylococcus aureus (Gram-positive bacteria, commercially available) and Escherichia coli (Gram-negative bacteria, commercially available). Staphylococcus aureus strains and Escherichia coli strains were added to the nutrient broth for culture to prepare two bacterial broths. Uranium adsorption resin was added to the bacterial broth at a dosage of 20 mg uranium adsorption resin per ml of bacterial broth. The bacterial broth without resin was used as a control. The two groups of nutrient broths were placed in a constant temperature shaker and cultured at 37°C and 130 rpm for 12 hours. The activity of the bacterial culture was determined by the dilution plate count method. The number of colonies formed on the plate was counted, and the inhibition rate was calculated using formula (1).
[0062]
[0063] Where: c0—the number of colonies on the plate cultured in broth without adding uranium adsorption resin; c a —The number of colonies on the plate cultured in broth with uranium adsorption resin added; R1—the inhibition rate of uranium adsorption resin.
[0064] Ball milling test
[0065] Tianchuang Powder SQM-0.5 ball mill was used for ball milling and the ball milling rate was tested.
[0066] Example 1 and Comparative Examples 1-2
[0067] 1. Preparation of uranium adsorption resin
[0068] 1. Preparation of ternary copolymer microspheres
[0069] a. Prepare the aqueous phase: Mix 200 mL of deionized water, 2 g of gelatin and 20 g of sodium chloride, and stir until the solute is dissolved to prepare the aqueous phase.
[0070] b. Prepare the organic phase: Mix acrylonitrile and alkyl acrylate to obtain a mixed solution. Take 20 g of the mixed solution and mix it with an appropriate amount of divinylbenzene to obtain a mixture. Mix the mixture, toluene and benzoyl peroxide in a weight ratio of 100:100:1, and stir until the solute is dissolved to prepare the organic phase.
[0071] c. Pour the organic phase into the aqueous phase in a ratio of 1:3 by volume, react at 80°C for 4 hours, and cure at 85°C for 10 hours. Wash the cured product with deionized water three times. Use ethanol as the extractant and Soxhlet extraction to extract the washed product, remove toluene as a porogen, and obtain ternary copolymer microspheres.
[0072] 2. Preparation of aminated microspheres
[0073] 5 g of ternary copolymer microspheres and an appropriate amount of ethylenediamine were added to 200 mL of toluene solvent, and the mixture was stirred at 100 °C for 16 h. After the reaction, the solid product was filtered out and washed with deionized water for 3 times. The washed solid product was vacuum dried at 45 °C for 24 h to obtain aminated microspheres.
[0074] 3. Preparation of functionalized microspheres
[0075] Add 5 g of aminated microspheres to 200 mL of reaction solvent. Add 2 mL of catalyst and an appropriate amount of 2-bromobenzimidazole in sequence under stirring, and stir at 60 ° C for 24 hours. After the reaction is completed, filter out the solid product and wash the solid product with deionized water three times. The washed solid product is vacuum dried at 45 ° C for 24 hours to obtain functionalized microspheres.
[0076] 4. Preparation of uranium adsorption resin
[0077] a. Prepare a reaction solution: add hydroxylamine hydrochloride to a mixture of 200 mL of methanol and deionized water (the volume ratio of methanol to deionized water is 1:1), and adjust the pH value of the solution to 7 with potassium hydroxide to obtain a reaction solution.
[0078] b. Mix 5 g of functionalized microspheres with the reaction solution and stir the reaction at 75°C for 24 h. After the reaction is completed, filter out the solid product and wash the solid product 3 times with deionized water. Immerse the washed solid product in a potassium hydroxide solution with a mass concentration of 2.5 wt%, shake at 50°C to obtain the product. Filter out the obtained product and wash it 3 times with deionized water to obtain a uranium adsorption resin.
[0079] 2. Performance Test
[0080] The uranium adsorption resins prepared in Example 1 and Comparative Examples 1-2 were subjected to uranium adsorption capacity test, antibacterial performance test and ball milling test. The specific parameters and test results are shown in Table 1.
[0081] Table 1
[0082] Example 1 Comparative Example 1 Comparative Example 12 Acrylonitrile dosage (g) 18 18 18 Alkyl acrylate types Methyl acrylate Methyl Methacrylate Methyl acrylate Amount of alkyl acrylate (g) 2 2 1.5 Mixed liquid (g) 20 20 20 Amount of divinylbenzene (g) 20.9 23.3 20.9 Ternary copolymer microspheres (g) 5 5 5 Ethylenediamine dosage (g) 5 5 5 Amination microspheres (g) 5 5 5 2-Bromobenzimidazole dosage (g) 8 9 10 catalyst Triethylamine Triethylamine Pyridine Reaction solvent Methanol Toluene N,N-Dimethylformamide Functionalized microspheres (g) 5 5 5 Amount of Hydroxylamine Hydrochloride (g) 15 15 15 Potassium hydroxide solution oscillation time (h) 3 5 4 Uranium adsorption capacity (mg / g) 19.1 20.6 18.9 Staphylococcus aureus inhibition rate (%) 97.02 96.37 96.65 Escherichia coli inhibition rate (%) 96.45 96.02 95.77 Ball milling rate (%) 91.8 91.2 90.4
[0083] It can be seen from Table 1 that the uranium adsorption resin prepared by the present invention has both high adsorption capacity and high antibacterial rate when adsorbing uranium in seawater. In addition, the uranium adsorption resin of the present invention also has a high ball milling rate, good mechanical strength, and can extend the service life.
[0084] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be thought of by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing a uranium adsorption resin, comprising the following steps: 1) 80 to 98 parts by weight of acrylonitrile and 2 to 20 parts by weight of alkyl acrylate are mixed to form a mixed solution, and then the mixed solution is mixed with 10 to 45 parts by weight of divinylbenzene to obtain a mixture; wherein the number of alkyl carbon atoms of the alkyl acrylate is 1 to 5; 100 parts by weight of the mixture, 60 to 200 parts by weight of a porogen and 0.5 to 2 parts by weight of an initiator are mixed to form an organic phase; gelatin, sodium chloride and water are mixed in a weight ratio of 1 to 3:10 to 30:100 to 300 to obtain an aqueous phase; the organic phase and the aqueous phase are mixed in a volume ratio of 1:2 to 1:5, reacted at 60 to 85°C for 2 to 6 hours, and then cured at 70 to 90°C for 8 to 12 hours to obtain ternary copolymer microspheres; wherein the porogen is selected from at least one of toluene and isooctane; the initiator is selected from at least one of benzoyl peroxide and azobisisobutyronitrile; 2) reacting the ternary copolymer microspheres with ethylenediamine at 60 to 120° C. for 1 to 24 hours to obtain aminated microspheres; wherein the mass ratio of the ternary copolymer microspheres to ethylenediamine is 1:0.2 to 1:2; 3) reacting the aminated microspheres with 2-bromobenzimidazole in a reaction solvent containing a catalyst at 40 to 80° C. for 10 to 48 hours to obtain functionalized microspheres; wherein the mass ratio of the aminated microspheres to the 2-bromobenzimidazole is 1:0.5 to 1:3; the reaction solvent is a C1 to C5 alkyl alcohol, and the catalyst is a tertiary amine containing three C1 to C5 alkyl groups; 4) adding the functionalized microspheres to a solution containing an amine oximation reagent, reacting at 60 to 80° C. for 8 to 48 hours to obtain a uranium adsorption resin; wherein the mass ratio of the functionalized microspheres to the amine oximation reagent is 1:1 to 1:6; and the amine oximation reagent is selected from at least one of hydroxylamine hydrochloride and hydroxylamine sulfate.
2. The preparation method according to claim 1, characterized in that: In step 1), the weight ratio of gelatin, sodium chloride and water is 2-3:20-30:200-230.
3. The preparation method according to claim 1, characterized in that: In step 2), the ternary copolymer microspheres react with the ethylenediamine in toluene.
4. The preparation method according to claim 1, characterized in that: In step 3), the C1-C5 alkyl alcohol is a C1-C3 normal alkyl alcohol.
5. The preparation method according to claim 4, characterized in that: The C1-C5 alkyl alcohol is selected from at least one of methanol and ethanol.
6. The preparation method according to claim 1, characterized in that: The tertiary amine containing three C1-C5 alkyl groups is triethylamine.
7. The preparation method according to claim 1, characterized in that: The preparation method of the solution containing the amine oximation reagent is as follows: An amine oximation reagent is added to a mixture of methanol and water, and the pH value of the mixture is adjusted to 6.5-7.5 with an alkali metal hydroxide solution to prepare a solution containing an amine oximation reagent; wherein the volume ratio of the methanol to water is 1:0.5-1:
2.
8. The preparation method according to claim 1, characterized in that: In step 4), the reactant obtained after the reaction is immersed in an alkali metal hydroxide solution with a mass concentration of 1 to 5 wt%, and shaken at 25 to 60° C. for 2 to 8 hours to obtain a uranium adsorption resin.
9. The uranium adsorption resin prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The antibacterial rate of the uranium adsorption resin on Staphylococcus aureus is more than 96.8%; the antibacterial rate on Escherichia coli is more than 96.2%; and the ball milling rate of the uranium adsorption resin is more than 91.5%.
10. Use of the uranium adsorption resin according to claim 9 in extracting uranium from seawater.
Citation Information
Patent Citations
Benzimidazole-amidoxime fiber as well as preparation method and application thereof
CN113713783A